2004
DOI: 10.1128/jcm.42.12.5783-5792.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genome Diversity of Pseudomonas aeruginosa Isolates from Cystic Fibrosis Patients and the Hospital Environment

Abstract: Pseudomonas aeruginosa is a gram-negative rod that is ubiquitous in nature. P. aeruginosa is also the quintessential opportunistic pathogen, causing a wide variety of infections in compromised hosts. In cystic fibrosis patients, P. aeruginosa is the leading cause of death. In this study, the evolutionary genetic relationships among 17 P. aeruginosa isolates were examined by comparative sequence analysis of the housekeeping gene encoding malate dehydrogenase and the chaperone groEL. The P. aeruginosa isolates e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
139
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 53 publications
11
139
0
Order By: Relevance
“…The low incidence of the multi-substrate protease (27%) in this study was in agreement with Finnan et al [33].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The low incidence of the multi-substrate protease (27%) in this study was in agreement with Finnan et al [33].…”
Section: Discussionsupporting
confidence: 82%
“…The frequency of the ExoU gene (18%) was similar to that obtained by Feltman et al [31] and Bradbury et al [32], however, it was relatively lower than that reported by Mitov et al [30] with a frequency of 30%. Moreover, the proportion of isolates (9%) having both genes was in agreement with Finnan et al [33] and Mitov et al [30], suggesting that the isolates with dual expression of both genes are increasing compared with earlier studies that showed a low number of such isolates (down to one isolate from a total of 115 isolates) [31]. ExoS is known to modify bacterial invasion while ExoU is recognized for inducing cytotoxicity and is more detrimental than ExoS toxin [31,34], thus, the presence of strains producing both toxins found in this study could indicate the emergence of highly virulent strains with mixed invasive-cytotoxic genotype.…”
Section: Discussionsupporting
confidence: 79%
“…Five PAO1 transcription factors were also absent, two having the lysR family signature (PA0207 and PA2220) and one, vqsM (PA2226), with 47% similarity to the essential quorum-sensing regulator OruR. As a group, therefore, all nine strains isolated from these two patients share attributes seen as characteristic of CRI in the cystic fibrosis lung (20,22,80): loss of certain genes whose products, by virtue of being secreted from or situated at the cell surface, offer targets for the immune system and loss of others whose products help mediate quorum sensing.…”
Section: Vol 79 2011 Secondary Infection and Mutator Activity In Cfmentioning
confidence: 99%
“…When studied in vitro, some of the most highly transcribed genes in P. aeruginosa biofilms belong to a filamentous Pf1-like bacteriophage (Pf phage) (5,6). The Pf prophage is also prevalent among clinical P. aeruginosa isolates from people with CF (7)(8)(9)(10)(11)(12)(13), and approximately 10 7 Pf phage per ml has been detected in the sputum of people with CF, where they interact with host polymers, such as mucin, to increase viscosity (14). These observations suggest that Pf phage may play a role in infection pathogenesis.…”
mentioning
confidence: 99%